2012
DOI: 10.2337/dc11-1684
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Urinary Full-Length and Ectodomain Forms of Megalin in Patients With Type 2 Diabetes

Abstract: OBJECTIVEMegalin, an endocytic receptor in proximal tubule cells, is involved in the mechanisms of albuminuria in diabetic nephropathy (DN). To develop efficient novel biomarkers associated with the pathogenesis of DN, we investigated urinary megalin excretion in type 2 diabetes.RESEARCH DESIGN AND METHODSSandwich enzyme-linked immunosorbent assay systems were established with monoclonal antibodies against the NH2 (amino [A]-megalin assay) and COOH (C-megalin assay) termini of megalin to analyze urinary forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 42 publications
6
75
0
Order By: Relevance
“…It has also been reported that cystatin C is filtered by glomeruli and metabolized in proximal tubular cells by binding to megalin in a Ca 2+ -dependent manner (14). Ogasawara et al (37) reported that urinary megalin was increased in correlation with the severity of type 2 diabetic nephropathy, likely leading to reduced metabolism of cystatin C in tubuli. These reports suggest that increases in urinary cystatin C excretion in diabetic patients may be one of the mechanisms involved in the dissociation of eGFR cys and C in .…”
Section: Discussionmentioning
confidence: 97%
“…It has also been reported that cystatin C is filtered by glomeruli and metabolized in proximal tubular cells by binding to megalin in a Ca 2+ -dependent manner (14). Ogasawara et al (37) reported that urinary megalin was increased in correlation with the severity of type 2 diabetic nephropathy, likely leading to reduced metabolism of cystatin C in tubuli. These reports suggest that increases in urinary cystatin C excretion in diabetic patients may be one of the mechanisms involved in the dissociation of eGFR cys and C in .…”
Section: Discussionmentioning
confidence: 97%
“…Megalin and cubilin function together in the reabsorption of proteins, including IgG and albumin, in the proximal tubule (43,44). Impairment of megalin function in diabetes has been suggested, even in the early stages of diabetes in animal models and in patients (45). Megalin expression can be severely downregulated due to protein over-load in diabetes, via activation of the renin-angiotensin system and increased TGF-ÎČ and TNF-α signaling in the lumen of the proximal tubular cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of urinary A-megalin and C-megalin was performed as previously described [21, 22]. In brief, 90-”L urine samples were mixed with a 10-”L solution (2 mol/L Tris-HCl, 0.2 mol/L EDTA, 10% Triton X-100, pH 8.0), and incubated for 1 min at room temperature for the C-megalin assay and for 3 h at 50°C for the A-megalin assay, to allow reactions between the capture monoclonal antibodies immobilized on the ELISA plates and the carboxy- and amino-terminal portions of megalin, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The intra- and inter-assay coefficients of variation were less than 10%. Urinary concentrations of Cr, N-acetyl-ÎČ-D-glucosaminidase (NAG), and ÎČ 2 -microglobulin were measured using an automated instrument (7170S; Hitachi High-Technologies Corp., Tokyo, Japan) with CRE-S (Denka Seiken Co., Ltd., Gosen, Japan), N-assay L NAG NITTOBO (Nittobo Medical Co., Ltd., Tokyo, Japan), and BMG-Latex (Denka Seiken Co., Ltd., Gosen, Jappan) kits, respectively, as previously described [21]. As a marker for oxidative stress in urine, urinary 8-OHdG was measured by ELISA (Japan Institute for the Control of Aging, NIKKEN SEIL, Co., Ltd., Shizuoka, Japan), as previously described [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation